Urban densities and transit: an analysis of Cape Town's integrated rapid transit system from 2010-2016 with specific focus on the Western Corridor. - Wilson, Melissa (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.